Development of An E-Pocket Book Using The Canva Application to Train Students Scientific Literacy Skills - Komaria, Siti; Al habib, Ismul Mauludin; Putri, Hanif Rafika (Universitas Pendidikan Mandalika, 2025)
This study aims to develop a Canva-based e-pocket book for enhancing science literacy skills among students. The Research and Development (R&D) method was employed, utilizing the ADDIE model. This study concentrates on developing science literacy skills in conjunction with Biology curriculum materials, particularly in the chapter concerning plant organs, which necessitates comprehension of scientific concepts and their practical application in daily life. The instruments consisted of validation questionnaires, science literacy tests, and interviews. Data analysis involved qualitative descriptive and quantitative statistical analysis. Results showed showed that the e-pocket book media was very feasible (89.7%) and effective in improving students' science literacy skills with the category of